Ecotourism development through biodiversity potential identification and community perception in the protected forest on Buano Island, Western Seram, Maluku, Indonesia - Martha Ekawati Siahaya; Paulus Matius; Marlon I Aipassa; Yaya Rayadin; YOSEP RUSLIM; Hendrik S.E.S Aponno (Society for Indonesian Biodiversity, 2021)
Abstract. Siahaya ME, Matius P, Aipassa MI, Rayadin Y, Ruslim Y, Aponno HSES. 2021. Ecotourism development through biodiversity potential identification and community perception in the protected forest on Buano Island, Western Seram, Maluku, Indonesia. Biodiversitas 22: 3179-3191. Forest as part of a large ecosystem has an important meaning and role in supporting living systems. Various great benefits can be obtained from the forests through its functions as a provider of water resources for humans and the environment, the ability of carbon sequestration, oxygen suppliers in the air, global climate regulators, and tourism service providers. The community has important role and participation in ecotourism that are different from other forms of tourism. Perception is a fundamental element that needs to be known before planning several activities that will involve the local community. This study aims to identify the potential of flora and fauna in the protected forest area for tourist attraction and analyze the Buano island community’s (Western Seram District, Maluku Province, Indonesia) perception of ecotourism development activities. The vegetation data were collected using the combination of the path method and the compartmentalized line method. The method used for collecting wildlife data in the field is the line transect method as well as direct and indirect observations. Meanwhile, data related to community perceptions were collected through questionnaires and interviews. The results show that the villages on Buano island have biodiversity and cultural potential that could be developed as ecotourism attractions. In addition, the community’s perception supported that they strongly agree on the development of ecotourism in the villages of Buano island.